Characteristics of glaucoma therapy with prostaglandin analogues nowadays - I.B. Alekseev; A.V. Volkova; L.I. Alekseeva (РМЖ "Клиническая офтальмология")
I.B. Alekseev1, A.V. Volkova1, L.I. Alekseeva2 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2I.M. Sechenov First Moscow State Medical University (Sechenov University), Moscow, Russian Federation Ocular hypotensive prostaglandin analogues (PGAs) are prodrugs that penetrate the cornea and become biologically active after hydrolysis by corneal esterase. They reduce intracranial pressure by increasing the uveoscleral outflow of aqueous humour and decreasing the outflow resistance. PGAs remain relevant as the first-line therapy drugs for patients with newly diagnosed glaucoma. The obvious exposure drawbacks of eye drops with preservatives have become prerequisites for the use of preservative-free medicines. Currently, it is recommended to use eye drops with preservatives less commonly, in the ideal case — only preservative-free products. In turn, the production of preservative-free drugs requires suitable carriers for the medicinal substance delivery — special vials (that do not depressurize when used) or monodoses. At present, reusable polymer dropper bottles have been developed, equipped with a valve that excludes the fluid intake return, a nozzle with ant ibacterial elements and an embedded sterilizing air filter. In the pharmaceutical market, travoprost is presented in the dosage form of eye drops, 0.04 mg/mL. This drug implements the described mechanism of drug storage and delivery. The review presents a meta-analysis on the comparative efficacy and tolerability of travoprost. Preservative-free travoprost presence on the pharmaceutical market in a special vial expands the range of available anti-glaucoma drugs. Keywords: glaucoma, hypotensive therapy, preservative-free dosage forms, prostaglandin analogues, travoprost. For citation: Alekseev I.B., Volkova A.V., Alekseeva L.I. Characteristics of glaucoma therapy with prostaglandin analogues nowadays. Russian Journal of Clinical Ophthalmology. 2022;22(3):175–180 (in Russ.). DOI: 10.32364/2311-7729-2022-22-3-175-180.